Public sector austerity cuts in Britain and the changing discourse of work-life balance - Lewis, Suzan; Anderson, Deirdre A.; Lyonette, Clare; Payne, Nicola; Wood, Stephen (SAGE, 2016)
The relative importance of economic and other motives for employers to provide support for work–life balance (WLB) is debated within different literatures. However, discourses of WLB can be sensitive to changing economic contexts. This article draws on in-depth interviews with senior human resources professionals in British public sector organizations to examine shifting discourses of WLB in an austerity context. Three main discourses were identified: WLB practices as organizationally embedded amid financial pressures; WLB practices as a strategy for managing financial pressures; and WLB as a personal responsibility. Despite a discourse of mutual benefits to employee and employer underpinning all three discourses, there is a distinct shift towards greater emphasis on economic rather than institutional interests of employers during austerity, accompanied by discursive processes of fixing, stretching, shrinking and bending understandings of WLB. The reconstructed meaning of WLB raises concerns about its continued relevance to its original espoused purpose.
Keywords: austerity; discourse; flexible working; human resource management; work–life balance (WLB)